PERAN SEKOLAH DALAM PENGUATAN KARAKTER PEDULI LINGKUNGAN PADA SISWA (Studi Kasus di SMK Muhammadiyah Kartasura) - Purwatiningsih, Endang (Sebelas Maret University (UNS), 2018)
This study aims to describe the strengthening of character in students care for the environment in SMK Muhammadiyah's debt. This type of research is a qualitative single case study with strategy. Data source this study informants, places, events, and documents. Engineering data collection research using interviews, observation, and documentation. The validity of the data in this study using triangulation techniques and sources. Data analysis using interactive models, Miles and Huberman. The results of this research proves that the school's role in strengthening environmental care character embodied in five steps: 1) gives advice or direction on students about the value of the characters care for the environment; 2) provides socialization on student to keep school garden; 3) involve students in creating or fix a garden equipment; 4) involves students in a group of pickets clean grounds; and 5) provide penalties on students who break the rules to clean up the Park and area schools.